Nurse practitioners, canaries in the mine of primary care reform. Issue 6 (June 2016) - Contandriopoulos, Damien; Brousselle, Astrid; Breton, Mylaine; Sangster-Gormley, Esther; Kilpatrick, Kelley; Dubois, Carl-Ardy; Brault, Isabelle; Perroux, Mélanie
Highlights: Successful NPs integration will require significant changes to primary care models. What if NPs were the "canary in the coal mine" of primary care reform? NPs may be catalysts to disruptive but desirable changes in healthcare systems. Abstract: A strong and effective primary care capacity has been demonstrated to be crucial for controlling costs, improving outcomes, and ultimately enhancing the performance and sustainability of healthcare systems. However, current challenges are such that the future of primary care is unlikely to be an extension of the current dominant model. Profound environmental challenges are accumulating and are likely to drive significant transformation in the field. In this article we build upon the concept of "disruptive innovations" to analyze data from two separate research projects conducted in Quebec (Canada). Results from both projects suggest that introducing nurse practitioners into primary care teams has the potential to disrupt the status quo. We propose three scenarios for the future of primary care and for nurse practitioners' potential contribution to reforming primary care delivery models. In conclusion, we suggest that, like the canary in the coal mine, nurse practitioners' place in primary care will be an indicator of the extent to which healthcare system reforms have actually occurred.